An assessment of the diagnostic criteria for sessile serrated adenoma/polyps: SSA/Ps using image processing software analysis for Ki67 immunohistochemistry - Fujimori Yukari; Fujimori Takahiro; Imura Johji; Sugai Tamotsu; Yao Takashi; Wada Ryo; Ajioka Yoichi; Ohkura Yasuo (BMC, 2012)
Abstract Background Serrated polyps belong to a heterogeneous group of lesions that are generally characterized morphologically. This type of lesion is thought to be the precursor of sporadic carcinomas with microsatellite instability, and probably also the precursor for CpG island-methylated microsatellite-stable carcinomas. For practical purposes, according to the 2010 WHO classification, the diagnostic criteria for sessile serrated adenomas/polyps (SSA/Ps) was established by the research project "Potential of Cancerization of Colorectal Serrated Lesions" led by the Japanese Society for Cancer of the Colon and Rectum. The aim of this study was to evaluate the validity of the morphologic characteristics established in Japan by using immunohistochemical staining for Ki-67. Methods To calculate the target cells, 2 contiguous crypts which could be detected from the bottom of the crypt to the surface of the colorectal epithelium were selected. To validate the proliferative activity, we evaluated the percentage and the asymmetrical staining pattern of Ki67 positive cells in each individual crypt. To examine the immunoreactivity of Ki67, computer-assisted cytometrical analysis was performed. Results SSA/Ps had a higher proliferative activity as compared to hyperplastic polyps (HPs) based on the difference in incidence of Ki67 positive cells, and the former also exhibited a significantly higher asymmetric distribution of these cells as compared to HPs, even in lesions with a diameter <10 mm. Conclusion We conclude that assessment of the pathological findings of SSA/Ps, including crypt dilation, irregularly branching crypts, and horizontally arranged basal crypts (inverted T- and/or L-shaped crypts) is appropriate to show a significantly higher proliferative activity as compared to HPs. Further, the use of two-dimensional image analysis software is an objective and reproducible method for this type of histological examination. Virtual slides The virtual slides for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/6718091416698112